Kegiatan Sinau Bareng Sebagai Upaya Untuk Menarik Antusiasme Anak Usia Dini Terhadap Bermain dan Belajar di RW 008 Kelurahan Wonorejo, Kota Surabaya - Arieska Wahyu Alprilia; Nur Rochman Dwi Iswanto (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Children's education is a critical aspect in shaping the future of society. This article discusses the importance of learning with children as an effective way to enhance their educational experience. Holistic learning is an educational approach that recognizes that a child's development is not limited to academic achievement only, but involves other aspects such as physical, emotional and social interactions. The main goal of holistic education is to develop children as a whole, including life skills, values and deep understanding of themselves and their surroundings. This activity is carried out through active and collaborative interaction. Adults have an important role in creating a constructive learning environment, stimulating creativity, and developing positive emotional relationships. Joint activities such as reading books, simple experiments, and listening to music can be effective media for facilitating intellectual and social growth for young children. This learning is carried out by including elements of play and fun, which can stimulate the curiosity of young children and stimulate their willingness to learn. This “Sinau Bareng” activity shows that learning together with children can increase their intrinsic motivation, as well as form a solid character foundation for future academic achievements.